Basketball without borders? Similarities and differences among Continental Basketball Championships. [¿Baloncesto sin fronteras? Similitudes y diferencias entre los Campeonatos Continentales de baloncesto]. - Sergio José Ibáñez; Sergio González-Espinosa; Sebastián Feu; Javier García-Rubio (Ramón Cantó Alcaraz, 2018)
The analysis of technical-tactical performance indicators is an excellent tool for coaches, because it provides objective information on the actions of players and teams. The aim of this investigation was to study the performance indicators for the last continental basketball championships. Five continental championships played in 2015 were analysed for a total of 213 matches. The variables analysed were: ball possessions, point difference, points scored, one, two and three point throws attempted and scored, total and defensive and offensive rebounds, assists, steals, turnovers, blocks for and against, fouls committed and received, and evaluation. A descriptive analysis and performance profiles were carried out to characterise the sample. A one-way ANOVA and Bonferroni correction were used to identify the differences among championships. A discriminant analysis was performed to identify the performance indicators best characterising each analysed championship. The results show that there are differences among all the championships and all the performance indicators, except in three point throws scored and blocks. A specific play profile has been identified for each championship. The greatest performance profile differences were found between the Eurobasket and the Afrobasket championships, while the championships with the most similar performance indicator profiles were FIBA America and Asia Cup. These findings are useful for coaches when preparing the different possible scenarios depending on the championship and their respective opponent. Resumen El estudio de los indicadores de rendimiento técnico-tácticos son una gran herramienta para los entrenadores, pues proporciona información objetiva sobre las acciones del deportista y del equipo. El objetivo de esta investigación fue estudiar los indicadores de rendimiento en los últimos Campeonatos Continentales de Baloncesto. Se analizaron los 5 campeonatos continentales del año 2015, un total de 231 partidos. Las variables analizadas fueron: posesiones de balón, diferencia de puntos, puntos anotados, lanzamientos de uno, dos y tres puntos anotados y lanzados, rebotes totales, defensivos y ofensivos, asistencias, robos, pérdidas, tapones a favor y en contra, faltas cometidas y recibidas, y valoración. Se llevaron a cabo un análisis descriptivo y de perfiles de rendimiento para caracterizar la muestra. La ANOVA de un factor con la corrección de Bonferroni se utilizó para identificar las diferencias entre campeonatos. El análisis discriminante permitió identificar los indicadores de rendimiento que mejor caracterizan a cada uno de los campeonatos continentales. Los resultados ponen de manifiesto que existen diferencias entre todos los campeonatos en todos los indicadores de rendimiento, salvo en los tiros de 3 puntos anotados y en los tapones. Se identifica un perfil de juego específico para cada campeonato. Las mayores diferencias en los perfiles de rendimiento se encuentran entre el Eurobasket y Africabasket, mientras que los campeonatos con un perfil más parecido en los indicadores de rendimiento son el FIBA América y Asiabasket. Estos hallazgos son de utilidad para los entrenadores a la hora de preparar los diferentes escenarios posibles en función del campeonato y rival al que se enfrenten.